Plantar alimento ou combustível? Contradições das políticas públicas federais para a produção territorial no sertão baiano - Vinicius Navarro Morende; Sidnei Raimundo (Confins)
This paper intends to analyze the existing contractions in the incentive of Brazilian federal public power to the food production and to the production of biodiesel to the space of Bahia’s State dry lands. For that, the effects of the National Program of Production and Use of Biodiesel (PNPB) and the Brazilian Program of Food Acquisition (PAA) to the territorial formation of the Morro do Chapéu (BA) city was analyzed, specially, during the period between 2007 and 2012. The paper is based on the oral history methodology made through a series of interviews with family farmers that participated of the activities of both programs. The rising of employment and familiar incomes of family farmers and the intensification of technical basis in localities of the municipality are some results of the federal public action and the local productive and social organization. However, series of evidences present the challenges to the public programs development and to development of family farm in Brazil.